IMPROVING VOCABULARY MASTERY USING INSTAGRAM POLLING QUIZ FOR ELEVENTH GRADE STUDENTS AT SMKN 1 NGANJUK - Yuli Antika Nurhayati; Caltira Rosiana (Journal of English Language Education, 2025)
Background: The objectives of this study are, (1) to identify the challeenges of students' vocabulary mastery before using Instagram poll quiz for eleventh grade at SMKN 1 Nganjuk, (2) to analyze the development of students' vocabulary mastery after using Instagram poll quiz for eleventh grade at SMKN 1 Nganjuk, (3) to identify the significant difference between students' vocabulary mastery before and after using Instagram poll quiz as English learning media for eleventh grade at SMKN 1 Nganjuk. This research design uses a quantitative approach and this type of research is Quasi Experiment. This research design is pre-test and post-test (one group pre-test and post-test). The population of this research is grade XI students at SMKN 1 Nganjuk in the academic year 2023/2024. The sample of this study were students of class XI-PGIM 2. The sampling technique used convenience sampling technique. Based on the written test scores, students obtained an average pre-test score of 57 students with a classification of "Low" and an average post-test score of 86.5 with a classification of "Very Good". Based on the results of the analysis, it is known that the 5% significant level for DF = 35 obtained the value of t_count = 17.065 and t_table = 1.690, then t_count> t_table which means Ha is accepted. Thus, there is a significant difference between students' vocabulary mastery before and after being taught using Instagram Polling Quiz for grade XI students at SMKN 1 Nganjuk in the 2023/2024 academic year. Thus, the use of Instagram Polling Quiz can improve students' vocabulary mastery.